2014
DOI: 10.1007/978-3-319-07515-0_11
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Model of Mental Workload in Pilots Based on Multiple Experimental Measurements

Abstract: The present study attempted to establish an effective discrimination and prediction model that can be applied to evaluate mental workload changes in human-machine interaction processes on aircraft flight deck. By adopting a combined measure based on primary task measurement, subjective measurement and physiological measurement, this study developed both experimental measurement and theoretical modeling of mental workload under flight simulation task conditions. The experimental results showed that, as the ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In order to explain why we did not notice such an increase in the subsequent sessions, we provide the following explanation. We know that STD‐RR and SD2 showed contradicting sensitivities to workload compared with operator fatigue: They increased with operator fatigue and decreased with mental workload . However, mental workload only appears after a certain amount of time.…”
Section: Analysis and Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In order to explain why we did not notice such an increase in the subsequent sessions, we provide the following explanation. We know that STD‐RR and SD2 showed contradicting sensitivities to workload compared with operator fatigue: They increased with operator fatigue and decreased with mental workload . However, mental workload only appears after a certain amount of time.…”
Section: Analysis and Discussionmentioning
confidence: 78%
“…They also mentioned that some HRV measures such as HR and HRV showed contradicting sensitivities to workload compared with operator fatigue. In addition, we also found that STD‐RR and SD2 have similar contradicting sensitivities to workload and fatigue: STD‐RR and SD2 increased with the increasing of operator fatigue, whereas STD‐RR decreased with the increasing of mental workload and SD2 was significant lower in the high mental workload condition than in the low mental workload condition…”
Section: Analysis and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many studies across various domains demonstrate that physiological sensors can be used to predict operator workload (Charles and Nixon 2019). Heart rate and heart rate variability (HRV) metrics have been correlated with workload in many studies and application areas (Abdelrahman et al 2015;Cinaz et al 2013;McDuff et al 2014;Mehler et al 2012;Moses et al 2007;Sugimoto et al 2016;Sztajzel 2004;Wei et al 2014b;G. F. Wilson 2002).…”
Section: Introductionmentioning
confidence: 99%